2006
DOI: 10.1002/elps.200500864
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic vesicle proteins under conditions of rest and activation: Analysis by 2-D difference gel electrophoresis

Abstract: Synaptic vesicles are organelles of the nerve terminal that secrete neurotransmitters by fusion with the presynaptic plasma membrane. Vesicle fusion is tightly controlled by depolarization of the plasma membrane and a set of proteins that may undergo post-translational modifications such as phosphorylation. In order to identify proteins that undergo modifications as a result of synaptic activation, we induced massive exocytosis and analysed the synaptic vesicle compartment by benzyldimethyl-n-hexadecylammonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 43 publications
(48 reference statements)
1
30
0
Order By: Relevance
“…Although proteomic techniques have existed for several years and have already been successfully used in numerous neurological diseases [125][126][127][128][129] , most proteomic studies described in stroke are based on animal models [130][131][132] . Therefore, its application and development in the study of human biological samples is a major challenge for understanding the disease.…”
Section: Expert Commentary and Fi Ve-year Viewmentioning
confidence: 99%
“…Although proteomic techniques have existed for several years and have already been successfully used in numerous neurological diseases [125][126][127][128][129] , most proteomic studies described in stroke are based on animal models [130][131][132] . Therefore, its application and development in the study of human biological samples is a major challenge for understanding the disease.…”
Section: Expert Commentary and Fi Ve-year Viewmentioning
confidence: 99%
“…Among the 185 identified proteins, only 19% were identified by all three techniques. The authors further demonstrated that synaptic depolarization induced synaptic vesicle protein changes, which were partly caused by post-translational modifications such as phosphorylation [36]. Takamori et al identified a larger number of synaptic vesicle proteins (410 proteins) [10].…”
Section: Review LI and Jimenezmentioning
confidence: 97%
“…In particular, diVerential quantitative proteomics, the comparison of an experiment and its control, is very discriminating for proteins involved in the process studied (Wilm 2009). The development of diVerential gel electrophoresis (DIGE) allows the evaluation of diVerences in protein pattern and post-translational modiWcations in the synaptic vesicle proteome of diVerent functional origin (Burré et al 2006a). A proteomic strategy to compare, for example, the proteome of mutant mice to that of controls can involve either gel-based diVerence gel electrophoresis (DIGE, Marouga et al 2005;Tannu and Hemby 2006b) or tandem mass tag (for review, see Elliott et al 2009).…”
Section: Quantitative Mass Spectrometrymentioning
confidence: 99%